A Sociotechnical Systems Approach to Road Safety in a Low- and Medium- Income Country: Gauteng Province South Africa - Masuku, Freeman Nkululeko (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.